Agustín habla sobre Alipio y Nebridio: una nueva interpretación de conf. VI, 7, 11–10, 17 - Neer, Joost van (Augustinus, 2020)
In conf. VI, the younger Augustine – as described by his older self – is well on his way to conversion, even though he is not yet aware of this himself. His spell as a Manichaean had not given him what he had hoped to find, and he feared that the Catholics would prove equally disappointing. Confronted with this situation, he decided to consult his friends. After an evocation of the influence of Ambrose (conf. VI,1,1–6,10), to which he proved susceptible, and before dealing with the problems to which the resulting choice gave rise (conf. VI, 11,18–16,26): to continue to work or not, to marry or not, Augustine describes his encounters with Alypius and Nebridius in conf. VI, 7,11–10,17. In this section, which is very carefully composed with regard not only to form (structure), but also, and primarily, to content (argument), he summons up the impasse in which he finds himself, and describes it with the aid of two images: that of illness, and that of danger at sea. The argument that he develops is that of a crisis: when a person is ill, it sometimes happens that the patient’s condition must first deteriorate before it improves, just as someone in danger at sea must sometimes face even greater peril before he is able to escape. This is what Augustine describes in conf. VI, 7,11–10,17, and this ensures that conf. VI is not a book in which he comes to a standstill, but one in which a therapeutic delay is created that gives him the strength and courage to accept humility instead of pride, and to persevere on his journey towards conversion, described in conf. VIII. This article analyses and interprets the strategy that Augustine employs to achieve this.